Chronic Use of Statins and Their Effect on Prevention of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis - Mahamid, Mahmud; Watad, Abdulla; Bragazzi, Nicola L.; Wengrower, Dov; Wolff, Julie; Livovsky, Dan; Amital, Howard; Adawi, Mohammad; Goldin, Eran (Frontiers in Pharmacology, 2018)
Background and aims: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is one of the major complications of ERCP. Thus, several non-invasive as well as invasive strategies have been investigated as preventative therapies for PEP with various efficacy. Methods: We enrolled any patients who underwent ERCP both at the Shaare Zedek Medical Center in Jerusalem and EMMS Nazareth hospital. Association between use of statins and different variables were assessed with univariate tests (chi-squared for categorical variables). Predictors of incidence of PEP and severity of pancreatitis were computed using conditional logistic regression, correcting for potential confounding factors. Results: 958 subjects were analyzed. Average age was 62.04±21.18 years (median 68 years). Most of the patients were female (n=558, 58.2%), Jewish (n=827, 86.3%) and inpatients (n=631, 65.9%). Only few ERCPs were performed emergently (n=40, 4.2%). 27 patients repeated the exam. Overall incidence of PEP/hyperamylasemia was 16.8% (n=161); with a 5.6% (n=54) incidence of hyperamylasemia and a 11.2% (n=107) incidence of pancreatitis. Overall, 6 cases of severe pancreatitis were identified. The logistic regression analysis demonstrated that chronic use of statins is a protective factor in preventing development of PEP/hyperamylasemia (OR 0.436 [95%CI 0.303-0.627], p<0.001); Particularly, the PEP OR was of 0.318 [95%CI 0.169-0.597], p<0.001 and the hyperamylasemia OR was of 0.565 [95%CI 0.372-0.859], p=0.008. No significant predictor could be found for the risk of developing severe PEP. Conclusions: Our data supports the possibility of exploiting statins as preventive agents for PEP. However, further studies, mainly RCTs, are warranted in order to replicate our findings.